2022
DOI: 10.1177/09731342221096481
|View full text |Cite
|
Sign up to set email alerts
|

Is Screen Addiction a Problem Among Rural School-Going Adolescents? A Cross-Sectional Study in South Karnataka

Abstract: Background: Media, including mobile phones, computers, and social media, is a dominant force in the lives of adolescents, and has now penetrated the rural areas. Screen addiction (SA) is a pathological compulsive use of screen-based devices. Objectives: To estimate SA and its associated factors among school-going adolescents residing in a rural area in South Karnataka. Methods: A cross-sectional study was conducted among adolescents (10-19 years) in 4 schools of Solur Hobli, Ramanagara district, using a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Even parent-alone usage can lead to “technology interference,” 30 meaning parenting is affected and this predicts the child’s screen use. There may be a bidirectional link between screen time and mental health issues—Johnson et al 31 found that excess screen time is significantly higher among depressed individuals, whose parents had frequent fights and those who didn’t participate in outdoor play. Similarly, Magee et al 32 found that there is a bidirectional link between sleep and screen usage among children.…”
Section: Discussionmentioning
confidence: 99%
“…Even parent-alone usage can lead to “technology interference,” 30 meaning parenting is affected and this predicts the child’s screen use. There may be a bidirectional link between screen time and mental health issues—Johnson et al 31 found that excess screen time is significantly higher among depressed individuals, whose parents had frequent fights and those who didn’t participate in outdoor play. Similarly, Magee et al 32 found that there is a bidirectional link between sleep and screen usage among children.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson AR et al . [ 17 ] found that 20% of adolescents felt thoughtful with screens, 8% felt restless, moody, and anxious when not using them, 26% used screen devices to escape of problems or releasing irritable mood, 12% had depression, and 3.9% had screen addiction. Also, A study in Gwalior city among private school students estimated that 24% adolescents have moderate internet addiction and 6.3% had severe addiction.…”
Section: Discussionmentioning
confidence: 99%